2020
DOI: 10.3390/ijms21072356
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylation Inhibitors as Modulators of Regulatory T Cells

Abstract: Regulatory T cells (Tregs) are important mediators of immunological self-tolerance and homeostasis. Being cluster of differentiation 4+Forkhead box protein3+ (CD4+FOXP3+), these cells are a subset of CD4+ T lymphocytes and can originate from the thymus (tTregs) or from the periphery (pTregs). The malfunction of CD4+ Tregs is associated with autoimmune responses such as rheumatoid arthritis (RA), multiple sclerosis (MS), type 1 diabetes (T1D), inflammatory bowel diseases (IBD), psoriasis, systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 179 publications
0
34
0
Order By: Relevance
“…T-1 showed a decreased cell number ratio and abnormal signals related to histone binding and the histone acetyltransferase complex. This result indicates that T-1 may consist of CD4+ T cells and therefore experience a differentiating response to inflammation, as histone acetylation contributes to the expression of genes involved in regulatory T cell differentiation and function, including increased Foxp3 stability ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…T-1 showed a decreased cell number ratio and abnormal signals related to histone binding and the histone acetyltransferase complex. This result indicates that T-1 may consist of CD4+ T cells and therefore experience a differentiating response to inflammation, as histone acetylation contributes to the expression of genes involved in regulatory T cell differentiation and function, including increased Foxp3 stability ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…HDAC-1 has been shown to be upregulated in psoriatic skin. 72,73 Previous studies have shown that HDAC inhibition regulates Treg function 74 by increasing Foxp3 expression 75 and preventing production of IL-17A. 76 As Treg plays an important role in the pathogenesis of psoriasis, 77 HDAC may be important for immune regulation in psoriasis.…”
Section: Histone Methylationmentioning
confidence: 99%
“…Its expression is regulated epigenetically ( 125 ). Foxp3 associates with HAT (p300 or TIP60) ( 126 ) as well as HDAC (SIRT1 or HDAC5) ( 127 ) pointing HAT inhibitors (HATi) as potential drugs for inhibiting Treg function ( 128 ). In Treg, replacement of a repressor complex at the Foxp3 promoter by the HAT p300/CREB-binding protein-associated factor (PCAF) is key to enable permissive histone modifications and as such making the Foxp3 promoter accessible ( 129 ).…”
Section: The Immune Cell Epigenome In the Cancer Microenvironmentmentioning
confidence: 99%